Association between male infertility and prostate cancer: a systematic review and meta-analysis. Issue 4 (July 2021) - Laukhtina, Ekaterina; Mori, Keiichiro; Pradere, Benjamin; Shariat, Shahrokh F.
Abstract : Purpose of review: Male infertility has been shown to be associated with different maladies. The present systematic review and meta-analysis aimed to summarize the available evidence on the association between male infertility or childlessness and prostate cancer. Recent findings: The PubMed, Web of Science, and Scopus databases were searched according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement. Studies were deemed eligible if they compared males with known infertility or childlessness to the control group including fertile males with regards to the diagnosis of prostate cancer. Overall, ten studies met our eligibility criteria. Three studies found that infertility was associated with higher risk of prostate cancer, four studies – with a reduced risk of prostate cancer, and three studies found no association. The forest plot revealed that infertility was not associated with prostate cancer (odds ratio [OR]: 1.26, 95% confidence interval [CI] 0.63–2.54; P  = 0.5). Infertility was not associated with high (OR: 1.44, 95% CI 0.54–3.83; P  = 0.5) or low (OR: 0.99, 95% CI 0.43–2.27; P  = 0.9) grade prostate cancer. Summary: Infertility or childlessness were not associated with the risk of prostate cancer. The significant heterogeneity between the included studies supports the need for more granular research to guide/fine tune early detection guidelines based on fertility. Abstract : Supplemental Digital Content is available in the text